Progress in photoreceptor replacement therapy for retinal degenerative diseases - Yuxin Du; Yin Shen (Cell Insight)
Retinal degenerative diseases encompass a diverse range of eye conditions that result in blindness, many due to photoreceptor dysfunction and loss. Regrettably, current clinical treatments are frequently not overly effective. However, photoreceptor transplantation shows promise as a potential therapy for late-stage retinal degenerative diseases. This article will review the various donor cell sources for this transplantation, as well as the mechanisms and factors that impact donor cell integration and material transfer, donor cell maturation, and other auxiliary methods that can be combined with photoreceptor transplantation to treat these degenerative retinal diseases.